DESIGNING A SINGLE PHASE INVERTER TO CALCULATE PUBLIC ROADS LIGHTING EFFICIENCY USING SODIUM LAMP TYPES - Apriani, Yosi; Barlian, Taufik; Danus, Muhar; Sofian, Ian Mochamad; Hidayat, Fahmi (FRONTIERS: JURNAL SAINS DAN TEKNOLOGI, 2018)
An inverter is a circuit which converts the AC voltage into DC voltage. Current use of inverters is very large, especially in industries, offices and housing. Even though now there are many inverter markets, but many are used for household loads, no one uses an inverter for roads lighting system namely sodium lamp because it requires a high frequency and voltage Then the surveyors placed a single phase inverter from the sodium lamp. Single phase inverter tool designed produces a voltage of 10,000 V, Amperage current of 0.20 A and 2000 w Power when tested against overloaded and not overloaded inverter, the results are quite good but in the design and manufacture of a single phase inverter is still lacking, which is only able to start the initial lighting of the sodium lamp because the current is small and the resulting voltage is unstable.Keywords: Single phase inverter, electrical energy, public road lighting, sodium lamp.